2015
DOI: 10.3109/07357907.2015.1041642
|View full text |Cite
|
Sign up to set email alerts
|

Salivary Immunosuppressive Cytokines IL-10 and IL-13 Are Significantly Elevated in Oral Squamous Cell Carcinoma Patients

Abstract: Oral squamous cell carcinoma (OSCC) is considered to be one of the most fatal diseases worldwide, owing to its late diagnosis and lack of availability of established reliable biomarkers. The aim of this study was to highlight the significance of immunosuppressive cytokines as potential biomarkers in OSCC. Whole unstimulated saliva was collected from each individual (30 OSCC patients and 33 age- and gender-matched healthy controls). Immunosuppressive cytokines, including IL-4, IL-10, IL-13, and IL-1RA, were eva… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
77
3
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 79 publications
(81 citation statements)
references
References 56 publications
0
77
3
1
Order By: Relevance
“…Of note, the levels of IL-10 and IL-13 were significantly increased, whereas the level of IL-1RA was the highest in poorly differentiated OSCC lesions compared with well- and moderately differentiated OSCC lesions. 19 A similar study found that the levels of TNF-α were higher in moderately and poorly differentiated tumours than in well-differentiated and stage IV tumours. Moreover, there was also a positive correlation between the histological grading of OSCC and TNF-α.…”
Section: Diagnosis Of Oral Diseases By Salivamentioning
confidence: 84%
“…Of note, the levels of IL-10 and IL-13 were significantly increased, whereas the level of IL-1RA was the highest in poorly differentiated OSCC lesions compared with well- and moderately differentiated OSCC lesions. 19 A similar study found that the levels of TNF-α were higher in moderately and poorly differentiated tumours than in well-differentiated and stage IV tumours. Moreover, there was also a positive correlation between the histological grading of OSCC and TNF-α.…”
Section: Diagnosis Of Oral Diseases By Salivamentioning
confidence: 84%
“…High expression of IL-6 in OSCC cells has been suggested as a predictive factor of poor response to chemoradiotherapy (31). The anti-inflammatory cytokine IL-1RA, which competes with IL-1β by binding to the IL-1 receptor, is also found in elevated levels in the saliva of patients with OSCC (32). IL-1β is secreted by tumor cells and is a substrate of MMP9 (10).…”
Section: Discussionmentioning
confidence: 99%
“…48 IL10 is found in elevated levels in the saliva of patients with HNSCC and may impair dendritic cell function and protect tumor cells from cytotoxic T-cells. 38,49,50 LGALS9 encodes for galectin-9, which is associated with metastasis and immunosuppression and found in elevated levels of lung, kidney, liver, and breast carcinomas. 51 Galectin-9 has been suggested to play a role in tumor cell evasion by inducing apoptosis in Th1 cells and cytotoxic T-cells.…”
Section: Discussionmentioning
confidence: 99%